Accelerated Depreciation, Tax Allocation, and Cyclical Asset Expenditures of Large Manufacturing Companies - Livingstone, John Leslie (Journal of Accounting Research, 1969)
John Leslie Livingstone, Accelerated Depreciation, Tax Allocation, and Cyclical Asset Expenditures of Large Manufacturing Companies, Journal of Accounting Research, Vol. 7, No. 2 (Autumn, 1969), pp. 245-256